2000
DOI: 10.1021/jp000739v
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network Approach to Predict the Solubility of C60 in Various Solvents

Abstract: A multiparameter artificial neural network (ANN) approach was successfully utilized to predict the solubility of C60 in different solvents. Molar volume, polarizability parameter, LUMO energy, saturated surface, and average polarizability molecular properties were chosen to be the most important factors determining the solubilities. The results show that in a large number of solvents (126) the solubility decreases with increasing molar volumes of the solvents and increases with their polarizability and saturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 7 publications
0
38
0
Order By: Relevance
“…Both Marcus et al and Ruoff et al concluded that the solubility increased when the molar volume of solvents increased. However, Kiss et al [33] used several computed and experimental properties of solvents and multiparameter artificial neural network method to correlate solubility, and reported the solubility decreased with increasing molar volume. Fig.…”
Section: Parameters Of Fullerenementioning
confidence: 99%
“…Both Marcus et al and Ruoff et al concluded that the solubility increased when the molar volume of solvents increased. However, Kiss et al [33] used several computed and experimental properties of solvents and multiparameter artificial neural network method to correlate solubility, and reported the solubility decreased with increasing molar volume. Fig.…”
Section: Parameters Of Fullerenementioning
confidence: 99%
“…There are many different approaches to calculate and predict C60 solubility in organic solvents. Some of them are fully mechanistic [5][6][7][8][9], developed from the thermodynamical point of view; others are statistically based, with good correlation coefficients, but not transparent and complicated in interpretation [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Neural network has been previously used for gas solubility and phase equilibrium modeling [29,[35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Nowadays, models developed based on the neural network approach are considered as valuable models, only if thermodynamic models show some drawbacks in prediction of properties and/or phase behavior of a system (or when there is no available method).…”
Section: Introductionmentioning
confidence: 99%